Structure of the human RECQ1 helicase reveals a putative strand-separation pin. - Pike, A; Shrestha, B; Popuri, V; Burgess-Brown, N; Muzzolini, L; Costantini, S; Vindigni, A; Gileadi, O (2009)
RecQ-like helicases, which include 5 members in the human genome, are important in maintaining genome integrity. We present a crystal structure of a truncated form of the human RECQ1 protein with Mg-ADP. The truncated protein is active in DNA fork unwinding but lacks other activities of the full-length enzyme: disruption of Holliday junctions and DNA strand annealing. The structure of human RECQ1 resembles that of Escherichia coli RecQ, with some important differences. All structural domains are conserved, including the 2 RecA-like domains and the RecQ-specific zinc-binding and winged-helix (WH) domains. However, the WH domain is positioned at a different orientation from that of the E. coli enzyme. We identify a prominent beta-hairpin of the WH domain as essential for DNA strand separation, which may be analogous to DNA strand-separation features of other DNA helicases. This hairpin is significantly shorter in the E. coli enzyme and is not required for its helicase activity, suggesting that there are significant differences between the modes of action of RecQ family members.